Convergence analysis of the loping OS-EM algorithm for noisy data - Guo, Yao; Fu, Min; Wang, Jinping (Complex variables and elliptic equations, 2020)
In this paper, we modify the OS-EM algorithm with an overrelaxation. For noisy data, we focus on the convergence analysis for loping OS-EM algorithm and extend the noisy data in -norm space. We get some results by employing a stopping rule and show weak convergence of the iterates to solution of the equations.